Transformation of Religious Services in Marginalized Areas: Engineering the Cluster System Policy for the Deficit of Christian Teachers and Counselors in South Sumatra - Parluhutan Lumban Batu (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
This policy study is motivated by the low accessibility of religious services for Christians in marginalized areas of South Sumatra Province, characterized by a chronic gap in the ratio of religious instructors to religious teachers. The main problem focuses on the distribution of functional personnel, which is centralized in urban areas, while transmigration and coastal areas experience a lack of sustainable education and spiritual guidance services. This study uses a descriptive qualitative methodology with a policy evaluation approach modeled after William N. Dunn, which includes criteria for effectiveness, efficiency, adequacy, equity, responsiveness, and technical feasibility. Using the Urgency, Seriousness, and Growth (USG) scoring technique, it was found that the inequality in human resource distribution is the most pressing issue requiring immediate intervention. The analysis results indicate that conventional recruitment mechanisms fail to address the extreme geographic barriers in South Sumatra. Therefore, this study recommends policy engineering through the implementation of a